Evaluation of social capital among students of Isfahan University of Medical Sciences in 2016 - Farajzadegan, Ziba; Heidari, Kamal; Samoei, Rahele; Tavakolifard, Negah (Social Determinants of Health, 2018)
Background: Social capital includes a series of issues and values, which is potentially in relation with social groups and organizations. Due to the importance of social capital as a determining factor in the health, this study aimed to evaluate the social capital in the students of the Isfahan University of Medical Science. Methods: This survey was the first phase of a survey that was carried out in Isfahan University of Medical Sciences on 700 students. Students were selected by a stratified random sampling method. Data on social capital of students were collected using Bullen questionnaire. For data analysis, IBM SPSS Statistics for Windows, Version 22.0. software was used. Results: The mean (SD) score of social capital of the students in this study were 62.11 (14.6), in which the lowest score belonged to the cooperation domain and the highest one belonged to the identity. The most important factors that related to the social capital of the students, included the gender (male: 58.82 (15.87) vs. female: 65.44 (15.87), P=0.028), residency (dormitory: 62.89 (14.3), live with family: 62.22 (14.27), personal home: 50.53 (20.63), P=0.006) and educational level (doctorate degree: 60.48 (13.79) vs. bachelor degree: 63.27 (15.07), P=0.019). Conclusion: The results of this study showed that the social capital score of college students was in a moderate level and policymakers need to design interventions in order to improve students' social capital especially in the level of their participation in the society.